Biodegradable PTLGA Terpolymers versus Collagen Implants Used as an Adjuvant in Trabeculectomy in Rabbit Eye - Niu, Weiran (J Ophthalmol, 2015)
Purpose. To evaluate the effectiveness and safety of three biodegradable terpolymers prepared from L-lactide, trimethylene carbonate, and glycolide (PTLGA) as an aid for trabeculectomy compared with the Ologen (OLO). Methods. Trabeculectomy was carried out on rabbits with implantation made from OLO or three PTLGA terpolymers. Intraocular pressure (IOP) was recorded 1, 2, 3, and 6 months postoperatively and bleb evaluations were performed using ultrasound biomicroscopy (UBM) 3 months after surgery, optical coherence tomography (OCT) every month, and transmission electron microscopy (TEM) six months after surgery followed by histological examination 1, 2, 3, and 6 months postoperatively. Result. IOP was significantly reduced in all groups after surgery. There were no significant differences in the IOL between groups at any time after implantation. There was no significant difference between the groups examined by OCT, UBM, and TEM. Exposure of the implant was observed in one eye from the OLO group and one eye in the P1. Subconjunctiva hyperblastosis was observed in one eye from group P3 and two eyes from the OLO group. Conclusions. Subconjunctival implantation of filtering devices made from PTLGA may present a safe and effective additional surgical tool for the treatment of filtering surgery. Fewer complications were observed in the group with P2 implants compared to other groups.